South Boston, My Home Town The History of an Ethnic Neighborhood - O'Connor, Thomas H., 1922-2012; Kennedy, Lawrence W., 1952-; Project Muse.; Project Muse. (2019)
An engaging yet objective look at the 350 year old history of Southie, a neighborhood that has survived largely unchanged since the early days of immigrant Irish families and old time political bosses. Originally published by Quinlan Press in 1988 and reprinted by Northeastern University Press in 1994. With a new foreword by Lawrence W. Kennedy.
Introduction -- From Colony to Community -- The Immigrant Tide -- Forming a Neighborhood -- Pensulia Politics -- "My Home Town" -- Photographs -- Changing Times -- Under Siege -- Looking Ahead.
Reprint of 1994 edition with new foreword.
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-No Derivatives 4.0 International License
Originally published: Boston : Quinlan Press, ©1988.
Includes bibliographical references (pages [247]-254) and index.
Description based on print version record.
Keywords: Massachusetts -- Boston -- South Boston; Massachusetts -- Boston; Boston (Mass.) -- Ethnic relations; Boston (Mass.) -- History; South Boston (Boston, Mass.) -- Ethnic relations; South Boston (Boston, Mass.) -- History; Irish Americans; Ethnic relations; Irish Americans -- Massachusetts -- Boston -- History; History; Electronic books; Electronic books